Carbon nanotubes/Al2O3 composite derived from catalytic reforming of the pyrolysis volatiles of the mixture of polyethylene and lignin for highly-efficient removal of Pb(ii). Issue 60 (24th November 2021) - Wang, Zhanghong; Qin, Kun; Wang, Zhikang; Shen, Dekui; Wu, Chunfei
Abstract : The coked catalysts derived from catalytic reforming of the pyrolysis volatiles of polyethylene, lignin and their mixture were developed as low-cost and high-efficient carbon materials-containing composites to remove heavy metal ions from water. Abstract : In the present study, the coked catalysts derived from catalytic reforming of the pyrolysis volatiles of polyethylene (PE), lignin (LG) and their mixture were developed as low-cost and environmentally-friendly carbon materials-containing composites to remove heavy metal ions from aqueous solution. The composites were thoroughly characterized by SEM, TEM, XRD, TGA and FT-IR and then their adsorption capability towards Pb(ii ) was investigated. It is found that curved cone-shape carbon nanotubes (CNTs) with abundant structural defects and O-containing surface functional groups, such as C–O, CO and –OH, can be obtained from the catalytic reforming of the mixture of PE and LG. The CNT-containing catalyst composite presents a superior adsorption capability towards Pb(ii ) when it is employed in Pb(ii ) removal. Adsorption isotherm and adsorption kinetics studies show that the adsorption process can be well simulated by the Langmuir isotherm and pseudo-second-order model, demonstrating that the adsorption is subjected to a homogeneous and chemical process. The calculated maximum adsorption capacity is as high as 146.08 mg g −1, which is much higher than most of the adsorbents reported. Moreover, thermodynamic analysis reveals that the adsorption is spontaneous and endothermic. Accordingly, the used catalyst from the catalytic reforming can be developed as a low-cost and highly-efficient adsorbent.